Focus on GH deficiency and thyroid function. Issue 1 (February 2017) - Giavoli, Claudia; Profka, Eriselda; Rodari, Giulia; Lania, Andrea; Beck-Peccoz, Paolo
Abstract : The relationships between GH system and hypothalamic–pituitary–thyroid axis are complex and not yet fully understood. The reported effects of GH administration on thyroid status of GHD patients have been remarkably divergent. This review will focus on the main studies aimed to clarify the effects of GH on thyroid function, firstly going through the diagnosis of central hypothyroidism and its possible pitfalls, then elucidating the possible contexts in which GHD may develop and examining the proposed mechanisms at the basis of interactions between the GH-IGF-I system and the hypothalamic–pituitary–thyroid axis.